Brain NAD Is Associated With ATP Energy Production and Membrane Phospholipid Turnover in Humans - Cuenoud, Bernard; Ipek, Özlem; Shevlyakova, Maya; Beaumont, Maurice; Cunnane, Stephen C.; Gruetter, Rolf; Xin, Lijing (Frontiers in Aging Neuroscience, 2020)
The brain requires a large amount of energy, mostly derived from the metabolism of glucose, which decreases substantially with age and neurological diseases. While mounting evidence in model organisms illustrate the central role of brain nicotinamide adenine dinucleotide (NAD) for maintaining energy homeostasis, similar data in human are sparse. This study explores the correlations between NAD, energy production and membrane phospholipid metabolism by 31-phopsphorous magnetic resonance spectroscopy (31P-MRS) across 50 healthy participants including a young (mean age 27.1-year-old) and middle-age (mean age 56.4-year-old) group. The analysis revealed that the brain NAD level and NAD+/NADH redox ratio were positively associated with ATP level and the rate of energy production, respectively. Moreover, a metabolic network linking NAD with membrane phospholipid metabolism, energy production, and aging was identified. An inverted trend between age and NAD level could also be detected. These results pave the way for the use of 31P-MRS as a powerful non-invasive tool to support the development of new therapeutic interventions targeting NAD associated phospho-metabolic pathways in brain aging and neurological diseases.